Musculoskeletal pain is common in competitive gaming: a cross-sectional study among Danish esports athletes - Michael Skovdal Rathleff; Christian Lund Straszek; Line Lindberg; Simon Bay Nielsen; Mads Damgaard; Ole Rolskov Sloth (BMJ Open Sport & Exercise Medicine, 2020)
Objectives The interest for competitive esports is growing. Little is known regarding musculoskeletal (MSK) pain among esports athletes. We aimed to investigate (1) the prevalence of MSK pain, (2) the association between MSK pain and esports-related training volume and (3) the association between MSK pain and physical activity levels.Methods Athletes aged 15–35 years who participated in structured esports through a computer-based game were eligible for inclusion. Participant demographics, hours/week spent on esports, self-report MSK pain sites, pain frequency, sleep, care-seeking behaviour and physical activity levels were collected through online questionnaires. The primary outcome was any MSK pain in the body during the previous week.Results Of 188 included athletes, 42.6% reported MSK pain. The most common pain site was the back (31.3%). Athletes with MSK pain participated in significantly less esports training compared with athletes without MSK pain (mean difference −5.6 hours/week; 95% CI −10.6 to −0.7, p=0.035). There was no significant difference in physical activity levels between groups (mean difference 81.1 metabolic equivalent of task-minutes/week; 95% CI −1266.9 to 1429.1, p=0.906).Conclusion Back pain is common among esports athletes. Athletes with MSK pain participated in less esports training compared with those without pain, suggesting a potentially negative effect of pain on esports participation.